KAJIAN DAMPAK LIMBAH KELAPA SAWIT TERHADAP KUALITAS PERAIRAN SUNGAI BUDONG-BUDONG SULAWESI BARAT: A Study on the Impact of Palm Oil Waste Industry on Water Quality in the Budong-Budong River, West Sulawesi - Syamriati Muallim (Universitas Hasanuddin, 2021)
The Budong-Budong River is widely used for community needs, especially clean water and water sources from the Regional Drinking Water Company (PDAM), so it is necessary to maintain its water quality so that it is following its designation. This research was conducted to determine the quality of the Budong-Budong River waters, which were affected by the activities of oil palm companies in Central Mamuju. The research objective was to determine the parameter values ​​of temperature, pH, DO, BOD, COD, TSS, Fatty Oil, sediment quality, macrozoobenthos ecological index, and status Budong-Budong river water quality affected by palm oil waste. The research was conducted at five observation points, namely company outlets, IPAL, before company, after company, creeks, rivers, each with three replications. Water samples were taken using horizontal dorm vans, and sediment samples taken using Ekman Grab. The results showed that the water quality status of the Budong-Budong River at the Outlets and WWTPs exceeded the palm oil industry of wastewater quality standards, while the waters before and after the company and river bodies were categorized as lightly polluted. This is due to the high levels of organic matter and other parameters at the Outlet and WWTP that have not undergone decomposition. Generally, aquatic sediment is clay textured, while the Diversity Index value tends to be heavily polluted according to water quality criteria based on diversity, while uniformity, macrozoobenthos dominance indicates unstable, stressed, and high dominance water conditions.